A review on the rhetorical structure and linguistic features of corporate annual reports - Sayyed Hussain, Shabnum; Mohamad Ali, Afida; Mohd Kasim, Zalina; Jalaluddin, Ilyana (Human Resource Management Academic Research Society, 2020)
Corporate annual report (CAR) is a communicative genre written by specialists in corporate companies. Over time, many linguistic studies have been conducted on this genre from various perspectives. This review paper critically examines studies on CARS, specifically on the rhetorical structure and linguistic features used in the genre. Based on the major findings of the studies reviewed in this paper, it can be argued that the writers of this professional discourse embellish the companies’ reputation with frequent usage of positive language features and minimal negative aspects. In addition, corporations claim credit and responsibility for positive events but in the case of negative events, responsibility is evaded. Finally, CARs are essentially reporting genres and structurally different from other promotional genres due to intentionally inter-discursive appropriations that are practiced in order to report and promote the companies.